Developing cognitive and motor decision-making skills through tactical principles and small-sided games in youth soccer - Machado, G.; González-Víllora, S.; Roca, A.; Teoldo, I. (International Journal of Performance Analysis in Sport, 2024)
This study aimed to verify the influence of 25 training sessions based on tactical principles and small-sided and conditioned games (SSCG) in developing cognitive and motor decision-making skills of U-12 soccer players. Participants were 25 U-12 elite male soccer players from a Brazilian first division national club. Perceptual-cognitive decision-making skills (quality and response time) were assessed with an objective video-based test (TacticUP®). Perceptual-motor decision-making skills (tactical efficiency) were assessed with the System of Tactical Assessment in Soccer (FUT-SAT). Both instruments were developed based on the same theoretical background (core tactical principles). The 25 training sessions were organised based on tactical principles and SSCG. The sessions were designed considering the individual needs to improve decision-making skills. Results showed improvements (p < .05) in: 1) perceptual-cognitive decision-making skills related to the decision-making time for both offensive and defensive actions and 2) perceptual-motor skills for defensive actions. We also found unexpected results for the quality of decision-making. It decreased for the defensive phase in post-test. We concluded that 25 training sessions based on core tactical principles and SSCG improved perceptual-cognitive related to decision time and perceptual-motor decision-making skills. Improvement of decision-making time apparently is related to improvement in tactical efficiency of U-12 soccer players.